Minimum Basin Algorithm: An Effective Analysis Technique for DNA Energy Landscapes - Kubota, Mitsuhiro; Hagiya, Masami (DNA Computing, 2005)
To design DNA nano-machines or analyze DNA molecular reactions, it is important to be able to predict the energy landscape of molecular structures and the energy barrier of a transition between structures on the landscape. Unfortunately, this is difficult for DNA molecules longer than 100 bases. In this paper, we propose an effective new technique for analyzing a structural transition over a DNA energy landscape. Imagine a very undulating landscape. Suddenly, water starts to gush out from one site and keeps flowing. How will the water surface expand over the landscape? Using a variant of Dijkstra’s and Jarník-Prim’s algorithms, we generate the shape of the basin from its formation process. The resulting basin contains the true energy barrier. Furthermore, a comparison between the basin feature and the corresponding actual chemical reaction shows that the basin can be used as a criterion to explain the reaction.